PENGARUH KOMPETENSI, INDEPENDENSI, TIME BUDGET PRESSURE TERHADAP KUALITAS AUDIT DENGAN ETIKA AUDITOR SEBAGAI MODERASI - Saifudin Saifudin; Aprih Santoso; Dione Jeanette Violita (POLITEKNIK LP3I JAKARTA, 2022)
This study aims to examine the effect of independence competence and time budget pressure on audit quality with auditor ethics as a moderating variable. The population in this study were all auditors who worked at the Public Accounting Firm in Semarang. Sampling was done using convenience sampling method and obtained a sample of 70 respondents. The primary data collection method was conducted through a survey method using a questionnaire. The data obtained were analyzed using using the absolute value difference test to test the effect of the moderating variable through SPSS 25. Based on the analysis and hypothesis testing, it can be concluded from the results of this study that competence has an effect on audit quality, while independence and time budget pressure have no effect on audit quality. Auditor ethics moderates the effect of competence and independence and time budget pressure on audit quality.Keyword : Competence, Independence, Budget,Â Ethics, Audit